The Long-Run Impacts of Public Industrial Investment on Local Development and Economic Mobility: Evidence from World War II - Andrew Garin; Jonathan Rothbaum (The Quarterly Journal of Economics, 2025)
Abstract This article studies the long-run effects of government-led construction of manufacturing plants on the regions where they were built and on individuals from those regions. Specifically, we examine publicly financed plants built in dispersed locations outside of major urban centers for security reasons during the U.S. industrial mobilization for World War II. Wartime plant construction had large and persistent effects on local development, characterized by an expansion of relatively high-wage manufacturing employment throughout the postwar era. These benefits were shared by incumbent residents; we find men born before World War II in counties where plants were built earned $1,200 (in 2020 dollars) or 2.5% more per year in adulthood relative to those born in counterfactual comparison regions, with larger benefits accruing to children of lower-income parents. The balance of evidence suggests that these individuals benefited primarily from the local expansion of higher-wage jobs to which they had access as adults, rather than because of developmental effects from exposure to better environments during childhood.